Safety of anti-influenza vaccination during pregnancy - Marta Kozłowska; Marcin Zaniuk; Piotr Wójcik; Monika Rogowska; Jan Tomczyk (Kazimierz Wielki University, 2020)
Flu, while seemingly harmless, is actually much more dangerous. These include ubiquity, high contagiousness and the possibility of serious complications. The flu is associated with serious complications, especially in pregnancy. It includes increased rates of miscarriage, stillbirths, neonatal deaths, premature births, and decreased birth weight. The flu vaccine is an effective and safe preventive measure. According to WHO anti-flu vaccine is recommended to women in any trimester of the pregnancy. Research shows that vaccination during pregnancy is safe and does not cause foetal or maternal complications. Moreover, maternal antibodies cross the placenta and can protect infant against influenza up to 6 months.  The most common reasons for refusing vaccines by pregnant women are hesitations and fear of adverse pregnancy outcome. Due to that it is important to increase the society's awareness about flu complications during pregnancy as well for women and for children. Successful immunization of the society requires improving its vaccination behaviour and can benefit in reducing frequency of adverse pregnancy outcomes.